MicroRNA‐122 can be measured in capillary blood which facilitates point‐of‐care testing for drug‐induced liver injury - Vliegenthart, A. D. Bastiaan; Berends, Cécile; Potter, Carmelita M. J.; Kersaudy‐Kerhoas, Maiwenn; Dear, James W. (British journal of clinical pharmacology, 2017)
Aims Liver‐enriched microRNA‐122 (miR‐122) is a novel circulating biomarker for drug‐induced liver injury (DILI). To date, miR‐122 has been measured in serum or plasma venous samples. If miR‐122 could be measured in capillary blood obtained from a finger prick it would facilitate point‐of‐care testing, such as in resource‐limited settings that have a high burden of DILI. Methods In this study, in healthy subjects, miR‐122 was measured by polymerase chain reaction in three capillary blood drops taken from different fingers and in venous blood and plasma (n = 20). miR‐122 was also measured in capillary blood obtained from patients with DILI (n = 8). Results Circulating miR‐122 could be readily measured in a capillary blood drop in healthy volunteers with a median (interquartile range) cycle threshold (Ct) of 32.6 (31.1–34.2). The coefficient of variation for intraindividual variability across replicate blood drops was 49.9%. Capillary miR‐122 faithfully reflected the concentration in venous blood and plasma (Pearson R = 0.89, P < 0.0001; 0.88, P < 0.0001, respectively). miR‐122 was 86‐fold higher in DILI patients [median value 1.0 × 108 (interquartile range 1.89 × 107–3.04 × 109) copies/blood drop] compared to healthy subjects [1.85 × 106 (4.92 × 105–5.88 × 106) copies/blood drop]. Receiver operator characteristic analysis demonstrated that capillary miR‐122 sensitively and specifically reported DILI (area under the curve: 0.96, P = 0.0002). Conclusion This work supports the potential use of miR‐122 as biomarker of human DILI when measured in a capillary blood drop. With development across DILI aetiologies, this could be used by novel point‐of‐care technologies to produce a minimally invasive, near‐patient, diagnostic test.